The kinetic energy of rain measured with an optical disdrometer: an application to splash erosion - Fernández-Raga, María (2020)
The present paper describes the procedures used to measure and compute the kinetic energy and various other rainfall characteristics as well as the concurrent splash erosion rates in a recently terraced forest plantation in Soutelo, north-central Portugal, from May to September 2007. This involved the use of an optical disdrometer, a standard automated rain gauge and two types of splash erosion measurement devices (i.e. 10 cups and 10 funnels). In the computation of the kinetic energy, the raindrops exceeding a specific threshold size were considered to not have a spherical shape. Without this correction for the shape of the bigger raindrops, the kinetic energy can be overestimated by 50% of its real value. A meteorological analysis indicated that four weather types with a western component produced more precipitation and kinetic energy, and, thus, a higher erosive power. The relationship between splash erosion and various rainfall characteristics set was analyzed in an exploratory manner, since the splash data only concern nine sampling periods. It showed well-defined relationships of increasing splash erosion with, amongst others, increasing total rainfall as well as total kinetic energy but these relationships require further analysis using additional data. The splash erosion figures obtained with the two types of devices showed a strong agreement but appeared to corroborate that the funnels are a more effective design than the cups.